Recovery of latent fingerprint on fired and unfired cartridge case using cyanoacrylate fuming followed by fingerprint powder and dye staining - Murugason, Malarvili A/P (2020)
Fingerprint on a cartridge case is a crucial evidence to link the perpetrator to firearm related evidence and the crime scene. However, such forensic evidence is often overlooked by the forensic investigator. A study was undertaken aiming to recover fingerprints using combination of cyanoacrylate fuming fingerprint enhancement technique with magnetic and regular powder dusting, as well as the basic yellow 40 (BY 40) florescent dying. In this study, the effectiveness of fingerprint enhancement technique on recovering fingerprints from the surface of unfired and fired cartridge cases at two different time duration between deposition of fingerprints and application of enhancement techniques was evaluated. From a total of 540 unfired and fired cartridge cases tested in this study, the best outcomes for enhancement of fingerprints was obtained through a combination of cyanoacrylate with basic yellow 40 technique. The usage of compatible lighting source would further increase the chances of obtaining the better marks. No significant difference was observed on the developed fingerprints on latent sebaceous and natural fingerprints, but eccrine fingerprints were found more difficult to develop using the enhancement technique. Upon firing, the fingerprints deposited on the cartridge cases were also less likely to be developed through enhancement technique, indicating the firing process had introduced damage on the ridge details. With extended time elapsed of fingerprint deposition, the chance of successfully development of fingerprints were also slightly reduced, suggesting the importance of fingerprint development within the shortestduration. To conclude, a combination of cyanoacrylate with basic yellow 40 was found successful in recovering fingerprints from unfired cartridge cases but lower chance of successfully development was reported with fired cartridge cases. It is hoped that this study had provided important clue on the presence of such important evidence in the crime scene, particularly forensic cases involving firearm. .